Research on Numerical Simulation of the Influence of Valley Down-cutting on Unloading of Bank Slope - LI Wancai; DENG Hui; SU Hang; DING Zhonghui; LU Bifeng; HAO Hao; LI Anrun (Renmin Zhujiang)
In order to obtain the influence on unloading of bank slope during the process of valley down-cutting, this paper takes the bank slope at the lower dam site of a hydropower station as the research object, and analyzes the stress field characteristics, displacement field and plastic zone evolution characteristics during the process of valley down-cutting by establishing the corresponding three-dimensional model for numerical simulation. The results show that during the process of valley down-cutting,in the horizontal direction, the stress inside the slope is greater than that of the free face of the slope with the same elevation; the displacement perpendicular to the channel increases gradually; the unloading depth continuously extends to the inside of the slope; and the existence of the ductile shear zone has a greater impact on the unloading of the rock mass.